Suppressed ferroelectric relaxor behavior of Mn-modified Ba(Zr0.3Ti0.7)O3 relaxor ceramics - Zhang, Qiwei (2014)
MnCO3-modified Ba(Zr0.3Ti0.7)O3 relaxor ferroelectric ceramics were fabricated by using the solid-state reaction method. The temperature dependences of electrical and dielectric properties of the ceramics were systematically investigated over the range −140 to 400 °C. The typical ferroelectric relaxor behavior of the Ba(Zr0.3Ti0.7)O3 ceramics was greatly suppressed by adding a proper amount of MnCO3. The suppressed relaxor behavior can be restored by annealing the samples in air, which is attributed to the presence of oxygen vacancies in the samples. In the paraelectric phase region, the low-frequency dielectric relaxations associated with oxygen vacancies are observed above room temperature, and increase with increasing of Mn content. Compared to the undoped Ba(Zr0.3Ti0.7)O3 ceramic, Mn-doped samples display excellent temperature stability in a wide temperature. The critical composition of x = 0.05 (MnCO3) not only exhibits a lower degree of ferroelectric relaxor behavior (ΔTm = 5.6 K), but also maintains a relatively higher tunability (66.9%@30 kV cm−1) than that of pure Ba(Zr0.3Ti0.7)O3 (ΔTm = 16.5 K, 49.6%@30 kV cm−1).